Pertukaran Sosial: Pergeseran Nilai Tradisi Ngantat Petolong di Era Modernisasi - Aulia, Nevia; Abdullah, Mirna Nur Alia; Nurbayani, Siti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The ngantat petolong tradition is very beneficial for the community, but currently the ngantat petolong tradition has undergone changes in the implementation process, which has caused the values contained in it to shift. The purpose of this research is to find out how the changes in the value of the ngantat petolong tradition that occurred in Penandingan Village, and what factors caused the changes. This research uses a qualitative case study method with data collection techniques using interviews, observation and documentation. The results showed that the value shift of the ngantat petolong tradition that occurred in the community, which was previously a tradition of mutual cooperation, became transactional. The factors that have a major influence on changes in the ngantat petolong tradition are advances in community knowledge and economic changes.